Recombinant expression, purification, crystallization and preliminary X‐ray diffraction analysis of the C‐terminal DUF490963–1138 domain of TamB from Escherichia coli. Issue 9 (1st September 2014) - Josts, Inokentijs; Grinter, Rhys; Kelly, Sharon M.; Mosbahi, Khedidja; Roszak, Aleksander; Cogdell, Richard; Smith, Brian O.; Byron, Olwyn; Walker, Daniel
Abstract : TamB is a recently described inner membrane protein that, together with its partner protein TamA, is required for the efficient secretion of a subset of autotransporter proteins in Gram‐negative bacteria. In this study, the C‐terminal DUF490963–1138 domain of TamB was overexpressed in Escherichia coli K‐12, purified and crystallized using the sitting‐drop vapour‐diffusion method. The crystals belonged to the primitive trigonal space group P 31 21, with unit‐cell parameters a = b = 57.34, c = 220.74 Å, and diffracted to 2.1 Å resolution. Preliminary secondary‐structure and X‐ray diffraction analyses are reported. Two molecules are predicted to be present in the asymmetric unit. Experimental phasing using selenomethionine‐labelled protein will be undertaken in the future.